Commumity Empowerment in Making Village Renstra in Merek District - Subhilhar; Sihombing, Marlon; Bahri, Saipul (ABDIMAS TALENTA: Jurnal Pengabdian Kepada Masyarakat, 2023)
Community empowerment in the field of village planning towards an independent village is part of an effort to improve the standard of living and the economy of the community in the village which is still in a condition that has not been able to escape from poverty and underdevelopment, when in fact the potential of the village at this time can make a significant contribution to improving the standard of living of the community. community income. Dokan Village as one of the tourist destinations in Karo Regency does not have a draft village development document that is oriented towards strengthening the village government. The Dokan Village Government tends to carry out normative development, as a result, the potential wealth of tourism in Dokan cannot be maximized. Research on community empowerment in the making of the village strategic plan in the District of Mark is able to answer matters relating to the reality related to the condition of village tourism, especially in Dokan Village, which shows that the development of tourist villages and tourism potential is not being managed optimally. The research objectives are (1) to describe the potential of Dokan tourism village in supporting village development; (2) to analyze the human resources of the Dokan Village community related to the knowledge factor of the Dokan Village community; (3) to analyze the level of empowerment in tourism village development and its correlation in increasing the income of rural communities; and (4) to formulate a village development strategy in improving the facilities, quality and management of Dokan Village tourism.